Ubiquitin Binding Protein 2-Like (UBAP2L): is it so NICE After All? - Guerber, Lucile; Pangou, Evanthia; Sumara, Izabela (Frontiers in Cell and Developmental Biology, 2022)
Ubiquitin Binding Protein 2-like (UBAP2L, also known as NICE-4) is a ubiquitin- and RNA-binding protein, highly conserved in metazoans. Despite its abundance, its functions have only recently started to be characterized. Several studies have demonstrated the crucial involvement of UBAP2L in various cellular processes such as cell cycle regulation, stem cell activity and stress-response signaling. In addition, UBAP2L has recently emerged as a master regulator of growth and proliferation in several human cancers, where it is suggested to display oncogenic properties. Given that this versatile protein is involved in the regulation of multiple and distinct cellular pathways, actively contributing to the maintenance of cell homeostasis and survival, UBAP2L might represent a good candidate for future therapeutic studies. In this review, we discuss the current knowledge and latest advances on elucidating UBAP2L cellular functions, with an aim to highlight the importance of targeting UBAP2L for future therapies.